Performance and carcass characteristics of grower pigs fed enzyme-supplemented dried cassava peel – maize cob composite meal - Anorue, Daniel Nnadozie (Brazilian Journal of Science, 2024)
A 90-day trial was carried out to evaluate the performance and carcass characteristics of grower pigs fed enzyme-supplemented dried cassava peel-maize cob composite meal (CP-MC). A total of 36 crossbreed male grower pigs (Large white) of about 16 weeks old with an initial body weight of 20.31 ± 0.61 kg-1 were randomly allotted into four groups of nine animals per treatment. Each treatment was further divided into three replicates consisting of three pigs in a completely randomized design. Pigs in treatment 1 were fed 0% CP-MC while CP-MC was used to replace maize at 40% (T2), 50% (T3), and 60% (T4). Diet was adequate in all nutrients, and clean water and feed were offered ad libitum. Results on growth performance showed that average daily weight gain was higher in T4 (0.34 kg) and T3 (0.33 kg), intermediate in T2 (0.26 kg), and lower in T1 (0.23 kg) (p < 0.05). Similarly, the best feed conversion ratio was found among pigs in T4 followed by T3, T2, and T1 (p < 0.05). Conversely, average daily feed intake was not influenced by the treatments (p > 0.05). Dressing percentages varied from 61.60-71.94% were significantly (p < 0.05) different among the treatments. Weights of the head, belly, limbs, back fat thickness, kidney liver, lungs, and spleen were significantly (p < 0.05) different among the treatments. In conclusion, the replacement of maize with CP-MC at 60% improved the weight of pigs without compromising the performance of animals.